CO2 Hydrates as a climate change mitigation strategy: Definition of stability zones in the Portuguese deep offshore - Bernardes, Luís (2012)
Storage of CO2 as hydrates in sub-seabed sediments has been pointed out as an alternative solution for the geological storage of CO2, particularly suitable for offshore areas where large ocean depths and low temperatures are reached at short distance from the onshore. This is the case for Portugal, where the continental shelf can be as narrow as 10 km. This paper presents the works conducted to identify the CO2 Hydrates Stability Zone, i.e. the areas where CO2 hydrates may form and remain stable, in the deep offshore of Portugal. The methodology adopted involved building maps of geothermal gradient, temperature of water, detailed bathymetry and conversion to hydrostatic pressure, and maps of sediment thickness. These maps were integrated in a GIS environment and a Fortran code was implemented to compute the thickness of the Hydrate Stability Zone, based on the pressure and the temperature conditions on the sub-seabed sediments. Preferential areas, where further studies should be conducted, were defined based on thickness and thickness variation of the Stability Zone, depth of the water column and distance from the main harbours.